Transcriptome analysis reveals heat tolerance of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) adults. (September 2018) - Lü, Jianhua; Huo, Mingfei
Abstract: Tribolium castaneum is one of the most destructive insects infesting cereals worldwide. Heat treatment, as one of the promising alternatives to chemical control, has been widely applied to disinfest empty grain storage spaces and food processing facilities. The influence of acclimation to sublethal high temperatures (36 and 42 °C for 10 h) on the heat tolerance of T. castaneum adults was investigated, and the transcriptome of T. castaneum adults was sequenced using Illumina sequencing technology for exploring the heat tolerance mechanism of T. castaneum adults. Acclimation to sublethal high temperatures significantly enhanced heat tolerance of T. castaneum adults. A total of 12, 596 unigene sequences were annotated with T. castaneum reference genome. A total of 280, 1134, and 948 DEGs were respectively identified in the 28A-36A, 28A-42A, and 36A-42A. Seventy-three commonly up-regulated genes and 36 commonly down-regulated genes were confirmed in response to heat tolerance from 28A to 36A, and 28A-42A. The results of RT-qPCR analysis were high significantly consistent with the RNA-seq analysis. These results offer a valuable information for future improving the effectiveness of heat treatment and exploring the evolution mechanism of the heat tolerance of T. castaneum adults. Highlights: Acclimation to 36 °C and 42 °C improved insect heat tolerance to lethal high temperature. The molecular mechanism of heat tolerance of T. castaneum by transcriptome analysis in combination with Real-time PCR was investigated.